Factors Influencing the Improvement of Students’ Writing Skill Through Peer Editing Technique - Merina, Yola; Autila, Rani; Yelliza, Yelliza (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This research investigated the students’ writing skill on recount text at session at session 2016 A English Department of STKIP West Sumatera. Some of them had difficulties in organization, content, grammar, mechanic, and vocabulary. Then, they really need lecturers’ correction in every step of their writing process. Therefore, the researcher applied peer editing technique as the focus of research to solve this problem. The purposes were to find whether peer editing technique can improve students’ writing skill on Recount Text and some factors influence the improvement. The methodology of research is a classroom action research (CAR). Researcher used writing test and questionnaire as the instruments. The finding of the research showed that the students’ writing skill of recount text improves through Peer Editing technique and there are four factors influenced the improvement.